2017
DOI: 10.1038/srep42341
|View full text |Cite
|
Sign up to set email alerts
|

Cockroach protease allergen induces allergic airway inflammation via epithelial cell activation

Abstract: Protease allergens are known to enhance allergic inflammation but their exact role in initiation of allergic reactions at mucosal surfaces still remains elusive. This study was aimed at deciphering the role of serine protease activity of Per a 10, a major cockroach allergen in initiation of allergic inflammation at mucosal surfaces. We demonstrate that Per a 10 increases epithelial permeability by disruption of tight junction proteins, ZO-1 and occludin, and enhances the migration of Monocyte derived dendritic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 64 publications
4
52
0
1
Order By: Relevance
“…We hypothesized that the observed induction of type 2 inflammation was due to protease‐induced damage to the sinonasal epithelium. Proteolytic damage to the sinonasal epithelium is known to induce the release of the alarmin IL‐33 . IL‐33 potently activates a variety of cell types involved in initiating and propagating type 2 responses, such as ILC2s, mast cells, basophils, and Th2 cells .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesized that the observed induction of type 2 inflammation was due to protease‐induced damage to the sinonasal epithelium. Proteolytic damage to the sinonasal epithelium is known to induce the release of the alarmin IL‐33 . IL‐33 potently activates a variety of cell types involved in initiating and propagating type 2 responses, such as ILC2s, mast cells, basophils, and Th2 cells .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, papain has limited relevance to ECRS in humans. Many common human allergens, however, demonstrate intrinsic protease activity, which is essential to their immunogenicity . Therefore, this model provides a valuable, physiologically relevant experimental system to study eosinophilic rhinosinusitis pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…The protease activity of natural Per a 10 was also important to initiate the allergic reaction at the mucosal surface. It increased the permeability of lung epithelium by the disintegration of cell junction proteins to enhance the migration of monocyte- derived dendritic cell precursors [119]. The functional property of native Per a 10 was also responsible for dislodging the CD23 and CD25 from the surface of PBMC, purified B cells and purified T cells.…”
Section: Molecular Allergology In Indiamentioning
confidence: 99%
“…Although cyclophilin has been reported to be IgE reactive, this is not likely to represent an important allergen as the pollen grains of periwinkle are not essentially airborne. The cockroach allergen Per a 10 was also expressed as a recombinant allergen [119, 124]. The rPer a 10 was IgE-reactive; however, it was observed that the protease activity in rPer a 10 was somehow attenuated, which resulted in reduced allergenic properties.…”
Section: Molecular Allergology In Indiamentioning
confidence: 99%
See 1 more Smart Citation